Sinteza glikogena v času po vadbi - Podlogar, Tim (Šport (Ljubljana), 2018)
One of the major limiting factors during prolonged endurance exercise is limited carbohydrate availability as a consequence of finite carbohydrates stores in the body. Carbohydrates are stored in the form of glycogen in muscles and in the liver. Given that full glycogen repletion takes ~24-h, have investigators over the past few decades explored ways how to augment glycogen resynthesis, as numerous athletes train or compete multiple times a day and thus have a limited time available for recovery. The present article offers literature review from this area of research and provides practical guidelines for athletes on when, how often, how much and in which form is the intake of carbohydrates optimal in the recovery period. By following these guidelines athletes should recover faster and consequently perform better in subsequent exercise bouts.
Keywords: fruktoza; glukoza; sinteza glikogena; športniki; telesna zmogljivost; vzdržljivostna vadba